Konsep Wahdat al-Wujud dan Wahdat al-Syuhud Menurut Syekh Yusuf Al-Makasari - Cucu Setiawan; Santi Yulianti; Maulani Maulani; Abdul Wasik (IAIN Bengkulu, 2022)
In Islam, religious beliefs can vary, as well as in the realm of Sufism. Understanding wahdatul form and wahdat as-syuhud for example. These two understandings are often discussed by several Sufism figures, one of which is Sheikh Yusuf al-Makasari. His thoughts on these two understandings were very influential in the archipelago. Not a few people think that the teachings of wahdatul embodiment or wahdat as-syhuhud are misguided understandings. However, if examined further, there is no error in these teachings, because basically the understanding between the two Sufis is taken from the Qur'an and hadith as well as other Sufi opinions. The method used in the research is a qualitative way, namely looking for reference sources both from journals and electronic books. Wahdatul embodiment and wahdat as-syuhud are understandings that were originally carried out by the Sufis to find a way so that they could be closer to Allah. By imitating one of the characters, Sheikh Yusuf, we can learn a lot from the story of his lifetime. Sheikh Yusuf is a Sufi who comes from the island of Makassar. In his understanding of Sufism, according to him, wahdatul form is different from wahdat as-syuhud. From wahdat as-syuhud, it does not invite much controversy from other Sufi scholars, unlike the case with wahdatul embodiment, there are still many who argue about its practice. But basically these two concepts are related to each other.